Perspectives of graduate student teaching assistants on value and meaning in their role - Natalie Elena Westwood; Diane S. Srivastava (Journal of Microbiology & Biology Education)
ABSTRACT There is increasing reliance on graduate student teaching assistants (GTAs) in undergraduate education, yet the impact of this role on graduate students is understudied. Previous research has focused on tangible outcomes such as skill development, rather than how GTAs value or find meaning in this role. Our study used a phenomenological approach rooted in self-determination theory to allow graduate students to describe their own experience of being GTAs and how they found value and created meaning through their role. We conducted interviews with five GTAs and used thematic analysis to describe their experiences. Generally, GTAs found the experience to be an important and positive aspect of their graduate program, intentionally using the experience to explore potential career paths and find belonging in the wider academic community. However, GTAs also identified several challenges, including pressure to exceed their contracted hours, and some GTAs saw these challenges as ethical dilemmas that were difficult to resolve. Overall, our study demonstrates the deep mindfulness that GTAs use when reflecting on their experiences and making choices within their role. Given the reflection that GTAs bring to their role, we recommend that those who train and work with GTAs actively support their professional development through centering GTA needs in order to enhance the experience of GTAs in the classroom.